5G MIMO Conformal Microstrip Antenna Design. (17th December 2017) - Wang, Qian; Mu, Ning; Wang, LingLi; Safavi-Naeini, Safieddin; Liu, JingPing
Abstract : With the development of wireless communication technology, 5G will develop into a new generation of wireless mobile communication systems. MIMO (multiple-input multiple-output) technology is expected to be one of the key technologies in the field of 5G wireless communications. In this paper, 4 pairs of microstrip MIMO conformal antennas of 35 GHz have been designed. Eight-element microstrip Taylor antenna array with series-feeding not only achieves the deviation of the main lobe of the pattern but also increases the bandwidth of the antenna array and reduces sidelobe. MIMO antennas have been fabricated and measured. Measurement results match the simulation results well. The return loss of the antenna at 35 GHz is better than 20 dB, the first sidelobe level is −16 dB, and the angle between the main lobe and the plane of array is 60°.